2018
DOI: 10.1177/0886260518786493
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of Health Risk Behaviors Among Brazilian Adolescent Victims of Family Violence

Abstract: Although recent studies have related the occurrence of violence in childhood and adolescence with the adoption of health risk behaviors, there are no studies that quantify this co-occurrence among adolescent victims of family violence. Our objective was, therefore, to investigate the co-occurrence of health risk behaviors in these adolescent victims. Data from the National School Health Survey, collected in 2015, were used. Co-occurrence of risk behaviors-involvement in fights, substance use (alcohol, drugs, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Considering the search results in the present review, studies have been found from cyber victimization and cyber aggression (38,39) aggression, family and adolescents (40,41)there are no studies that quantify this co-occurrence among adolescent victims of family violence. Our objective was, therefore, to investigate the co-occurrence of health risk behaviors in these adolescent victims.…”
Section: Results Of Aggression and Violence In The Ibero-american Con...mentioning
confidence: 95%
“…Considering the search results in the present review, studies have been found from cyber victimization and cyber aggression (38,39) aggression, family and adolescents (40,41)there are no studies that quantify this co-occurrence among adolescent victims of family violence. Our objective was, therefore, to investigate the co-occurrence of health risk behaviors in these adolescent victims.…”
Section: Results Of Aggression and Violence In The Ibero-american Con...mentioning
confidence: 95%
“…Among the analyzed behaviors, it was observed that RB, such as sedentary behavior and inappropriate food consumption, can co-occur, and the high prevalence of this co-occurrence was associated with sociodemographic, family, and behavioral factors 10,21 . In addition, the co-occurrence of the analyzed behaviors corroborates the findings of a survey that investigated adolescents from 89 countries to determine clustering patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents who reported having mothers with higher education level had a greater chance of co-occurrence of RB for the three assessed models. Higher maternal education level can also represent a higher income level, which can lead to greater family purchasing power, providing, for example, access to games, electronic devices, and unhealthy food 10 . One of the possible explanations is that higher education levels represent mothers who probably work outside their homes and, therefore, tend to have less control over what adolescents do in their spare time 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of violence can cause immediate or late consequences (Krug et al, 2002). Studies suggest that violence during childhood and adolescence are associated with the adoption of risky behaviors (alcohol, drugs, and tobacco use and inadequate food consumption) (Marques et al, 2018; Marques et al, 2019) and mental health outcomes (anxiety, depression, and other psychopathology) (Hillberg et al, 2011; MacMillan et al, 2001; Norman et al, 2012).…”
Section: Introductionmentioning
confidence: 99%